HUBUNGAN KADAR KOLESTROL LOW DENSITY LIPOPROTEIN PLASMA DENGAN KADAR HIGH SENSITIVITY C-REACTIVE PROTEIN PADA REMAJA OBES - Budiono, Daniel (Universitas Sam Ratulangi, 2014)
Abstract: Atherosclerosis is the leading cause of mortality in the developed countries and in the future, it is predicted to be the leading cause of mortality in the developing countries. Low density lipoprotein, high sensitivity C-reactive protein, and obesity have been identified as risk factors of atherosclerosis. Obesity during childhood and adolescents tends to occur during adults life. The aim of this study is to know the levels of low density lipoprotein and high sensitivity C-reactive protein and the correlation between those two levels in obese adolescents. This observational cross sectional study design involved 17 obese adolescents and analyzed using Spearman Correlation Test. The results showed the mean levels of LDL was 123,0 mg/dL, and hs-CRP was 1,618 mg/L. Spearman correlation test showed significance value (p) was 0,024 and correlation significance value coefficient was 0,544. From the results can be concluded that the levels of low density lipoprotein levels in obese adolescents is in normal range, obese adolescents are associated with a moderate risk of cardiovascular disease at the future and there is a significant positive correlation between low density lipoprotein cholestrol levels and high sensitivity C-reactive protein levels in obese adolescents. Keywords : low density lipoprotein, high sensitivity c-reactive protein, obese adolescentsÂ Â Abstrak: Aterosklerosis merupakan penyebab kematian utama di negara maju saat ini, dan diprediksi akan menjadi penyebab kematian utama di negara berkembang di masa mendatang. Peningkatan kadar low density lipoprotein dan kadar high sensitivity C-reactive protein (hs-CRP) serta obesitas telah diidentifikasi sebagai faktor risiko aterosklerosis. Remaja yang mengalami obesitas cenderung tetap mengalami obesitas pada saat dewasa. Tujuan dari penelitian ini untuk mengetahui gambaran kadar kolestrol low density lipoprotein dan kadar high sensitivity C-reactive protein pada remaja obes, serta hubungan kadar low density lipoprotein dengan kadar high sensitivity C-reactive protein pada remaja obes. Penelitian ini menggunakan desain penelitian analitik observasional dengan pendekatan cross sectional terhadap 17 remaja obes. Nilai rerata kadar LDL pada remaja obes 123,00 mg/dL, dan nilai rerata kadar hs-CRP pada remaja obes 1,618 mg/L. Berdasarkan hasil penelitian, dapat disimpulkan remaja obes memiliki kadar LDL dalam rentang normal, remaja obes memiliki risiko sedang terkena penyakit kardiovaskular di masa mendatang dan terdapat hubungan positif yang signifikan antara kadar low density lipoprotein dengan kadar high sensitivity c-reactive protein pada remaja obes. Kata Kunci: low density lipoprotein, high sensitivity c-reactive protein, remaja obes